The Medievalism of Emotions in King Lear - Czarnowus, Anna (Multicultural Shakespeare: Translation, Appropriation and Performance, 2021)
King Lear exemplifies two cultures of feeling, the medieval and the early modern one. Even though the humoral theory lay at the heart of the medieval and the early modern understanding of emotions, there was a sudden change in the understanding of specific medieval emotions in Renaissance England, such as honour as an emotional disposition. Emotional expression also changed, since the late Middle Ages favoured vehement emotional expression, while in early modern England curtailment of any affective responses was advocated. Early modern England cut itself off from its medieval past in this manner and saw itself as “civilized” due to this restraint. Also some medieval courtly rituals were rejected. Expression of anger was no longer seen as natural and socially necessary. Shame started to be perceived as a private emotion and was not related to public shaming. The meaning of pride was discussed and love was separated from the medieval concept of charity. In contrast, in King Lear the question of embodiment of emotions is seen from a perspective similar to the medieval one. The article analyzes medievalism in terms of affections and studies the shift from the medieval ideas about them to the early modern ones.